[Alfréd Ruby 9]
around the Balaton with Trabant, swimming in the lake, camping Balatonföldvár, Balatonszárszó, Héviz open-air bath, Harkány cooking in stew-pot, Máriagyűd dedication festival, Villány, Mohács, Baja, Kalocsa, 1971 luggages to the trabant & Balaton again, Héviz, Balatonfüred, Siófok SZOT holiday-home, angler, badminton, swinging, at the lido, Siófok water tower,